Atrial high-rate episodes predict clinical outcome in patients with cardiac resynchronization therapy. (4th March 2017) - Jacobsson, Jonatan; Platonov, Pyotr G; Reitan, Christian; Carlsson, Jonas; Borgquist, Rasmus
Abstract: Objectives . Up to 50% of patients qualified for cardiac resynchronization therapy (CRT) have documented atrial fibrillation (AF) prior to CRT-implantation. This finding is associated with worse prognosis but few studies have evaluated the importance of post-implant device-detected AF. This study aimed to assess the prognostic impact of device-detected atrial high- rate episodes (AHRE), as a surrogate for AF. Design . Data were retrospectively obtained from consecutive patients receiving CRT. Baseline clinical data and data from CRT device-interrogations, performed at a median of 12.2 months after CRT-implantation, were evaluated with regard to prediction of the composite endpoint of death, heart transplant or appropriate shock therapy. Median follow-up time was 51 months post-implant. Results . The study included 377 patients. Preoperative AF was present in 49% and associated with worse outcome. The cumulative burden of AHRE at 12 months post-implant was an independent predictor of the primary endpoint. During the first 12 months after CRT-implantation, AHRE were detected in 25% of the patients with no preoperative diagnosis of AF. This finding was not associated with worse outcome. Conclusions . In CRT recipients, the cumulative burden of AHRE during the first year of follow-up was associated with worse long-term clinical outcome. Prospective trials are needed to determine if a rhythm control strategy is to be preferred in patients with CRT.